From DGCR8 expression analysis to diseased pathways in 22q11.2 deletion syndrome - Boz, Valentina; Di Rosa, Marianna; Pin, Alessia; De Martino, Eleonora; Faletra, Flavio; Baldo, Francesco; Magnolato, Andrea; Valencic, Erica (Frontiers in Immunology, 2025)
22q11.2 deletion syndrome (22q11.2DS) is the most prevalent microdeletion disorder, distinguished by markedly diverse clinical manifestations, with its underlying molecular mechanisms not yet fully elucidated. This study sought to examine the expression of the commonly deleted gene DGCR8 and its possible association with immune cell populations and cellular pathways involved in the immune response. We quantified DGCR8 mRNA levels, evaluated immune cell subsets, and conducted functional assays to measure S6-phosphorylation (PI3K-AKT-mTOR activity), H2AX-phosphorylation kinetics (DNA damage response), and STAT1 expression (interferon response) in 13 pediatric patients compared with healthy controls. Our findings indicate a reduced expression of DGCR8 in patients relative to controls, albeit with significant variability and notably low levels, as well as in one patient whose deletion did not include the DGCR8 gene. A notable positive association between DGCR8 expression and natural killer (NK) cell numbers was identified exclusively in the patient cohort, suggesting that NK cells may serve as a clinically biomarker for assessing microRNA dysregulation severity in 22q11.2DS. Nonetheless, the functional studies performed did not demonstrate substantial differences between patients and controls. In summary, this study validates altered DGCR8 expression and establishes a novel association with NK cells in patients with 22q11.2DS. It implies that factors beyond mere gene deletion may affect DGCR8 levels and highlights a positive correlation between DGCR8 expression and NK cell count. The identification of this relationship has immediate clinical implications, as routine flow cytometric assays of NK cells could potentially provide a biomarker for monitoring immune dysfunction in patients with 22q11.2DS.